Risk-Based Ultrasound Screening for Thyroid Cancer in Obese Patients is Cost-Effective - Cham, Stephanie (Mary Ann Liebert, Inc., 2014)
Background: A higher body mass index (BMI) is associated with more advanced stages of thyroid cancer. Screening obese patients for thyroid cancer has been proposed but has yet to be examined for cost-effectiveness. The objective of this study was to assess the cost-effectiveness of ultrasound (US) screening of obese patients for thyroid cancer. Methods: A decision-tree model compared cost savings for the following: (i) base case scenario of an obese patient with thyroid nodule found by palpation, (ii) universal US screening of all obese patients, and (iii) risk-based US screening in obese patients. Risk-based screening consisted of patients who had at least one of four major identified risk factors for thyroid cancer (family history of thyroid cancer, radiation exposure, Hashimoto's thyroiditis, and/or elevated thyrotropin). Patients with nodules underwent established treatment and management guidelines. The model accounted for recurrence, complications, and long-term treatment/follow-up for five years. Outcome probabilities were identified from a literature review. Costs were estimated using a third-party payer perspective. Sensitivity analyses were performed to examine the impact of risk factor prevalence and US cost on the model. Results: The resulted costs per patient were $210.73 in the base case scenario, $434.10 in the universal US screening arm, and $166.72 in the risk-based screening arm. Risk-based screening remained cost-effective until more than 14% of obese patients had risk factors and with a wide variation of US costs ($0–$1113). Conclusion: Risk-based US screening in selected obese patients with risk factors for thyroid cancer is cost-effective. Recommendations for screening this subgroup will result in cost savings and a likely decreased morbidity and mortality in this subpopulation with more aggressive disease.